Protective effect of sesame (sesamum indicum) seed oil against hypercholesterolemic in sprague-dawley male rats - ASLAM,Maria (2021)
Abstract To explore the protective effect of sesame seed oil (SSO) extracted from Til-06 sesame variety in Sprague-Dawley male rats against the management of hypercholesterolemia, the current two-phase study was conducted. In the first phase, oil was taken out from the sesame seeds (Til-06) and physicochemical analysis was carried out to find out the content of oil following by the evaluation of the quality attributes of extracted oil. In the second phase, efficacy was carried out to check the hyperlipidemic activity of sesame seed oil. Randomly distributed twenty (20) rats into 5 different groups with four (04) rats in each group and for 60 days fed as follow; the first group was fed on a basal diet, while the other groups were fed with 2, 4, 6 and 8% SSO plus basal diet. Blood samples were collected at the beginning and end of the study for biochemical study i.e. lipid profile which includes high-density lipoprotein (HDL-C), triglycerides (TG), low-density lipoprotein (LDL-C), total cholesterol (TC), and very-low-density lipoprotein (VLDL) and antioxidant status. Findings of the present study indicate that the oral administration of SSO significantly (P < 0.05) improved the antioxidant status with lower TC, LDL-C, TG, VLDL-C, and higher HDL-C values of hypercholesterolemic rats.